Atmospheric particulate polycyclic aromatic hydrocarbons from road transport in southeast Brazil - Allen, A. G. [UNESP]; da Rocha, G. O.; Cardoso, Arnaldo Alves [UNESP]; Paterlini, W. C. [UNESP]; Machado, C. M. D. [UNESP]; de Andrade, J. B. (Pergamon-Elsevier B.V. Ltd, 2008)
The Cubatao industrial complex of southeast Brazil is sited on a coastal strip bounded on the continental side by a mountainous scarp covered with tropical forest. Four cities have developed around the complex. The metropolitan region of São Paulo is located on a plateau above the scarp. The combination of the region's topography, the industrial installations, and an intensely trafficked road network causes widespread atmospheric pollution. In November 2004, measurements were made of the 16 polycyclic aromatic hydrocarbons designated as priority pollutants by the US Environmental Protection Agency, as well as of aerosol mass and ionic composition. Use of characteristic concentration ratios for emission sources show that tailpipe emissions from diesel vehicles was the main source of the compounds. This means that a shift from gasoline to ethanol as fuel in spark ignition engines will have only minor influence on atmospheric polycyclic aromatic hydrocarbon concentrations, despite very low emissions during ethanol combustion. on the other hand, reduction in emissions associated with increasing use of biodiesel in compression ignition engine fuel mixtures could significantly reduce atmospheric concentrations. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Polycyclic aromatic hydrocarbons; PM(10); Biofuels; Diesel; Ethanol; Precipitation scavenging